Die Entwicklung wichtiger Fischbestände in der Nordsee und im Nordatlantik. Ergebnisse der Herbstsitzung des Advisory Committees for Fishery Management des internationalen Rates für Meeresforschung - Hammer, Cornelius (1997)
The October meeting of the ACFM of ICES gave advice for a number of North-Atlantic fish stocks. The results of the most important stocks are given here from the perspective of German fishery management. The are chiefly North Sea plaice and sole, for which a reduction of 25 % of the fishing mortality (F) is recommended for 1998, North Sea saithe (minus 20 % in F), while North Sea cod is in the process of recovery and North Sea haddock is inside safe biological limits. The mackerel stock of the North Sea has not yet recovered, while the western mackerel stock as an entity has stabilised at a level of about 2.3 million t.